Longitudinal study on modulated corticospinal excitability throughout recovery in supratentorial stroke. (23rd March 2016) - Julkunen, Petro; Könönen, Mervi; Määttä, Sara; Tarkka, Ina M.; Hiekkala, Sinikka H.; Säisänen, Laura; Vanninen, Ritva; Karhu, Jari; Jäkälä, Pekka
Highlights: Corticospinal excitability is modulated over 6 months recovery in stroke. Asymmetry in CSE reaches normal levels after ∼1 month after stroke onset. Lesion size and severity correlate positively with reduced CSE. Abstract: Corticospinal excitability (CSE) is modulated by stroke-induced lesions affecting the brain. This modulation is known to be dependent on the timing of the evaluation, and strongest abnormalities are often found in the acute stage. Our study aimed to characterize changes in CSE asymmetry between the affected and the unaffected hemisphere (AH and UH) during the first month after stroke onset and at 6 month follow-up. Neuronavigated transcranial magnetic stimulation (nTMS) was used to assess the CSE of the abductor pollicis brevis (APB) muscle of the hand and tibialis anterior (TA) muscle of the leg in 16 patients over 5 time-points. AH excitability recovered significantly during 6 months, whereas interhemispheric asymmetry remained significant up to 1 month post-stroke in the APB muscle. Greater initial CSE was associated with good motor function at 6 months. The motor cortical excitatory recovery initiated within week of the stroke and was most prominent within 1 month after stroke onset. Lesion size correlated with CSE of the UH at 10 days, while overall severity of the symptoms correlated inversely with CSE of the AH. This study demonstrates the quick improvement in the CSE via estimation of interhemispheric asymmetry; however, the recovery in the asymmetry continues to normalize even after reaching the threshold for normal values in CSE.